Human uterine vasculature with respect to uterus transplantation: A comprehensive review. Issue 11 (24th August 2020) - Kristek, Jakub; Johannesson, Liza; Novotny, Robert; Kachlik, David; Fronek, Jiri
Abstract: Due to the novelty of uterus transplantation, data on preferable inflow and outflow of the graft are limited. This paper reviews the technique, type of vessels and the outcome. A systematic search of the PubMed database was conducted. We extracted and analyzed data on the arteries and veins utilized, types of anastomosis, types of donors, complications and the outcome. Thirty eight sources reported 51 human uterine transplantations, 10 graft thromboses and 25 live births. Inflow was established with two uterine arteries (UA) with/without the anterior division of the internal iliac artery in 62% ( n = 31) of cases, two UA arteries with a segment/patch of the internal iliac artery in 34% ( n = 17) of cases or two UA with a conduit in 4% of cases ( n = 2). Both cases with a conduit developed thrombosis ( n = 2). Arterial thrombosis/ischemia developed in 8 of the 51 cases. In 50% of cases with arterial thrombosis, atherosclerosis was identified as a possible cause. Outflow was established by two internal iliac veins with patches/segments in 27.5% of cases ( n = 14) followed by two utero‐ovarian veins in 25.5% ( n = 13). Venous thrombosis occurred in 3 of the 51 cases. Uterine arteries with/without anterior division of the internal iliac artery were the most frequent arteries used for inflow and produced the highest patency rate. The presence of atherosclerosis and complex arterial reconstruction was associated with a high rate of arterial thrombosis. None of the veins utilized in the procedures appeared to be superior. There are insufficient data to draw a definite conclusion.